Intra-seasonal variation of surface air temperature in Nepal Himalayas - UENO, KENICHI; POKHREL, ADARSHA P. (MAUSAM, 2002)
Intra-seasonal variation of surface air temperature observed by the automatic weather station at Syangpoche in Khumbu region, Nepal Himalayas, is analyzed. In the monsoon season, temperature was nearly constant with large decrease in insolation due to monsoon clouds. On the other hand, large intra-seasonal variation existed in the winter with increase in temperature associated with passing synoptic scale high-pressure system which disturb local circulation pattern as well as decrease in temperature due to the nighttime strong radiative cooling under the condition of snow covers. Monsoon clouds and deep valley system caused unique surface temperature variation.